IMPLIKATUR PERCAKAPAN TOKOH DALAM NOVEL LOVE IS PUNISHMENT KARYA WINDY IRIANTI - Alifa, Ramadhian; Amir, Johar; Wijayanti, Tuty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to: (1) Describe the types of conversational implicatures of characters in the novel Love Is Punishment by Windy Irianti which include general conversational implicatures and specific conversational implicatures; and (2) the principle of cooperation of characters in the novel Love Is Punishment by Windy Irianti which includes the maxims of quantity, quality, relevance, and implementation and (3) violations of the principle of cooperation of characters in the novel Love Is Punishment by Windy Irianti. This type of research is qualitative descriptive research. The research data are in the form of utterances, dialogues, and excerpts of conversations between characters that contain conversational implicatures. The data source for this research is the novel Love Is Punishment by Windy Irianti. Data collection was carried out through reading and note-taking techniques with the stages of intensive reading, identifying utterances containing implicatures, and classifying data according to the focus of the research. The research instrument was the researcher herself who was assisted by a conversational implicature classification table based on Grice's theory. Data analysis was carried out using the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results of the study show that: (1) the character dialogues in the novel Love Is Punishment contain general and specific conversational implicatures which are used to convey meaning indirectly; (2) in addition, the cooperative principle of the character's conversation contains the maxims of quantity, quality, relevance and implementation, and (3) violations of the cooperative principle of the four maxims are also found which are influenced by the context of the situation, the character's emotions, and the strategy for conveying meaning. Thus, conversational implicatures play an important role in building communication dynamics, character characterization, and conveying pragmatic meaning in the novel.